2020
DOI: 10.2217/crc-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of RAS Testing Over Time: Factors Influencing Mutation Rates in Metastatic Colorectal Cancer Patients

Abstract: Aim: Correct identification of RAS gene variants is key for targeted treatment decisions in patients with metastatic colorectal cancer. Published RAS mutation rates differ and could be influenced by several factors including testing methods. This study aimed to describe the performance of laboratories to correctly identify RAS variants over time and to understand how RAS testing has evolved in Europe. Materials & methods: Misclassification and test failure rates were calculated and related to the used test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Laboratories reported to frequently participate to EQA schemes to validate their methods, and train their personnel to perform the actions associated with validation or verification. Frequent participation to EQA as well as training in the form of workshops have previously been reported to exert a beneficial effect on test performance [28,29,31,47].…”
Section: Laboratories' Strategies For Validation and Verificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Laboratories reported to frequently participate to EQA schemes to validate their methods, and train their personnel to perform the actions associated with validation or verification. Frequent participation to EQA as well as training in the form of workshops have previously been reported to exert a beneficial effect on test performance [28,29,31,47].…”
Section: Laboratories' Strategies For Validation and Verificationmentioning
confidence: 99%
“…to the occurrence of resistance mechanisms upon progression to TKIs. Second, recent analysis in mCRC stressed that not all laboratories have well implemented rare RAS variants in exons 3 and 4, resulting in higher error rates [30,31]. Third, the analysis of underlying causes of incorrect tests revealed that laboratories mentioned insufficient method sensitivities or omission of rare variants in their kit to be at basis of the false negative results [32].…”
Section: Sample Selection and Reference Materialsmentioning
confidence: 99%
See 3 more Smart Citations